Edukasi Penyakit Degeneratif Pada Lansia di Rumah dan Medical Check-up sederhana di Dusun 1 Desa Suka Sari, Kec. Kabawetan, Kab. Kepahiang Tahun 2025 - Anabella, Tiara Syifa; Yolan , Leti; Fitriani , Selvi; Merlia , Olpi; Siptiani , Nopa; Susanti , Meri Epriana; Pebriani , Emi (Universitas Dehasen Bengkulu, 2026)
Degenerative diseases are common health problems among the elderly, arising from the natural aging process, unhealthy lifestyle habits, and long-term exposure to various risk factors. Limited knowledge regarding early symptoms, risk factors, and preventive measures often leads to poor awareness and delays in early detection among older adults. Therefore, health education and simple health screening are essential to enhance the elderly’s understanding and awareness of degenerative disease prevention. This activity was conducted door to door for 15 elderly residents in Dusun 1, Suka Sari Village. The intervention included health education using leaflets, two-way communication, and simple health checks in the form of blood pressure measurement. Elderly individuals who previously had limited understanding became more aware of their health conditions and the importance of early prevention. Blood pressure measurements also indicated the need for continuous monitoring, particularly related to hypertension risk.